Design, synthesis and evaluation of 4-phenyl-1,2,3-triazole substituted pyrimidine derivatives as antiproliferative and tubulin polymerization inhibitors - Dwivedi A.R.; Kumar V.; Yadav R.P.; Kumar N.; Jangid K.; Anand P.; Sharma D.K.; Barnawal S.; Kumar V. (My University, 2025)
Ligands binding to the colchicine domain of the tubulin protein act as tubulin polymerization inhibitors and arrest the cell cycle in G2/M phase. A series of 4-Phenyl-1,2,3-triazole substituted pyrimidine derivatives have been synthesized and evaluated for antiproliferative and antitubulin activities. In the series, AV-6 and AV-14 were found to be active against the three tested cancer cell lines wherein AV-6 displayed IC50 values of 1.2 µM, 5.5 µM, and 1.9 µM while AV-14 displayed IC50 values of 4.7 µM, 1.7 µM, and 1.4 µM against HCT-116, MCF-7 and HT-29 cell lines, respectively. These compounds were found to be non toxic to the normal cells (HEK-293). In the cell cycle analysis and JC-1 studies, these compounds induce mitocondria mediated apoptosis. In the tubulin polymerization inhibition studies, AV-6 displayed significant tubulin polymerization inhibition potential. In the molecular docking and simulation studies, these compounds fit well in the active site of colchicine. © 2022 Elsevier B.V.